2011
DOI: 10.1021/jp208209c
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxes of Thermodynamics of Swelling Equilibria of Polymers in Liquids and Vapors

Abstract: An automatic registration of the changing size of a single spherical microbead of a cross-linked polymer was applied for studying the swelling process of the bead by the sorption of vapors and/or liquids. Many representatives of all three basic types of polymeric networks, gel-type, hypercrosslinked, and macroporous, were examined. Only the first two display large volume changes and prove suitable for following the kinetics and extent of swelling by the above dilatometric technique. The results unambiguously p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The general nature of this phenomenon is explained by the fact that the absolute activity of any sorbate in its liquid form is always larger than in the form of its saturated vapor. Earlier study on the swelling of cross-linked polymeric beads led to another possible explanation of Schroeder’s paradox . The authors found that strain-relaxed gels with any solvent contents retain their volumes constant in the saturated vapor atmosphere, and they attributed this effect to the specificity of the polymer–solvent interactions in network polymers.…”
Section: Resultsmentioning
confidence: 99%
“…The general nature of this phenomenon is explained by the fact that the absolute activity of any sorbate in its liquid form is always larger than in the form of its saturated vapor. Earlier study on the swelling of cross-linked polymeric beads led to another possible explanation of Schroeder’s paradox . The authors found that strain-relaxed gels with any solvent contents retain their volumes constant in the saturated vapor atmosphere, and they attributed this effect to the specificity of the polymer–solvent interactions in network polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, the above consideration must be valid, to a more or less evident extent, for borders between any liquid and gaseous or solid phases, rather than just for borders between water (or aqueous solutions) and their vapors or immersed polymers. Indeed, Schroeder's effect was also shown to be characteristic of all organic solvents in combination with corresponding swelling polymers, without any exception [12].…”
Section: Role Of Interfaces In Transfer Of Sorbate Moleculesmentioning
confidence: 94%
“…A rather complete list of relevant references can be found in publications by Davankov and Pastukhov [12] and, in particular, by Jeck et al [13].…”
Section: Introduction Previous Work In the Fieldmentioning
confidence: 99%
See 2 more Smart Citations